On some locally finite groups which are sharply triply transitive - Heineken, H.; Ritthaler, R. (Український математичний журнал, 1991)
We classify the groups Г satisfying the folowing conditions: i) Г is locally finite; ii) Г if sharply triply transistive permutation group; iii) all elements of Г have fixpoint.